The 2019 parliamentary elections in India: democracy at crossroads? - Mitra, Subrata Kumar; Saxena, Rekha; Mukherjee, Pampa (Routledge, 2022)
"This book presents a comprehensive overview of India's electoral democracy and political system. It provides an in-depth analysis of the 2019 Parliamentary elections to explore three crucial facts of India's political life: the legitimacy of political competition as the only basis of power; elections as the only legitimate basis of political competition; and, political parties as the only legitimate agency to conduct political competition. The book argues that the vitality and resilience of India's electoral democracy remains high owing to large mass participation in elections that are competitive and relatively free and fair. The volume includes key theoretical, empirical, and comparative perspectives on parties and elections from experts, and covers all major political parties of India, along with the performance of many representative regional parties. It discusses themes such as elections and party competition in India; ideology, interest, religion and gender as they affect social mobilisation and political transaction; economic and politial change, and multiparty democracy; the dynamics of the Muslim vote; fluctuating electoral fortunes; and electoral campaigns and role of social media. This book will be an essential read for scholars and researchers of political science, political sociology, election studies, Indian politics, South Asian politics, and South Asian studies. It will also interest those in politics, public policy and governance, civil society organisations, media and journalism, and the general reader"--
Includes bibliographical references and index
Keywords: India -- Parliament -- Elections, 2019; India -- Politics and government -- 2014-; Aufsatzsammlung; Geschichte 2019; Parlamentswahl; Indien